ANTIDEPRESSANTS AS POTENTIAL ADJUVANTS IN TREATING CHRONIC PAIN AND PAIN INDUCED DEPRESSION - V.S.SARAVANAN; V.KRISHNARAJU (International Journal of Pharma and Bio Sciences, 2013)
Clinical studies have shown that people suffering from chronic pain are often also burdened by depression. Antidepressants are widely used to treat painful chronic rheumatic conditions but, contrary to neuropathic conditions, however, little is known about their mechanisms of action. This article reviews the available evidence on the efficacy and safety of antidepressants in major chronic pain conditions; namely, neuropathic pain, diabetic neuropathic pain, headaches, cancer pain, arthritic pain, irritable bowel syndrome (IBS) and fibromyalgia. Antidepressants exhibit a number of pharmacological actions: they block reuptake of noradrenaline and 5-hydroxytryptamine, have direct and indirect actions on opioid receptors, inhibit histamine, cholinergic, 5-hydroxytryptamine and N-methyl-D-aspartate receptors, inhibit ion channel activity, and block adenosine uptake. In summary, evidence supports the use of tricyclic antidepressants in neuropathic pain, diabetic neuropathic pain, headaches, cancer pain, arthritic pain, IBS and fibromyalgia.